PENGARUH BUDAYA REJANG TERHADAP PERENCANAAN KARIER SISWA DI SMA NEGERI 9 KOTA BENGKULU - HENI SULUSYAWATI; MELATI MELATI (Psikodidaktika, 2019)
This research is motivated by the discovery still rejang culture students who do not have a mature career planning, there are students who are confused rejang culture in choosing courses that will be selected to enter college. The purpose of this study was to determine the influence of culture on career planning rejang students. This research is a qualitative descriptive study, using natural setting approach. Collecting data using the technique of participant observation, unstructured interviews, and technical documentation. Analysis of data using Spradley models that domain analysis, taxonomic analysis, componential analysis, and analysis of the cultural theme. Based on the results of data analysis, then it can be explained several cultural factors that can influence student planning, namely 1) the habit of increasing decisions to improve, 2) influencing peers, 3) replacing work, 4) seeking and keeping high to advance.